Escaping the Exchange of Information: Tax Evasion via Citizenship-by-Investment - Dominika Langenmayr; Lennard Zyska (Center for Economic Studies and Ifo Institute (CESifo), 2021)
With (automatic) exchange of tax information among countries now common, tax evaders have had to find new ways to hide their offshore holdings. One such way are citizenship-by-investment programs, which offer foreigners a new passport for a local investment or a fixed fee. We show analytically that high-income individuals acquire a new citizenship to lower the probability that their tax evasion is detected through information exchange. Using data on cross-border bank deposits, we find that deposits in tax havens increase after a country starts offering a citizenship-by-investment program, providing indirect evidence that tax evaders use these programs.
Keywords: H26; H24; F53; K37; 330; citizenship-by-investment programs; tax havens; tax evasion